(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
Agricultural risks of mineral salt (Ca2+, Mg2+, K+, Na+, SO42- , Cl- , CO32- , HCO3- ) content in the water of the Voghji River catchment basin were assessed. Water sampling and hydrochemical analyses were implemented in July and September 2017. The results of the study showed that anthropogenic salt level in the Voghji River water site located downstream from Kapan Town and in the area of the Norashenik River mouth may have posed serious health risks to irrigated soils and crops.